Muzyka w edukacji wczesnoszkolnej (rekonesans badawczy nauczycieli) = Music in Early Childhood Education (research reconnaissance of teachers) - Kataryńczuk-Mania, Lidia; Cieślik, Adrianna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
In 1993 the curriculum imposed to the teacher of primary education the responsibilities in the range of integrated education (including conducting music lessons). Unfortunately, as many studies indicate, it did not improved students` results in the area of music due to the deficiencies of musical competence among teachers of younger ages. In the article the Authors present the issue on the basis of literature and research reconnaissance among teachers.
Keywords: nauczyciel edukacji wczesnoszkolnej; nauczanie muzyki; kompetencje nauczyciela; teacher of early childhood education; music teaching; teachers` competences